2015
DOI: 10.1002/prca.201400101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in the investigation of HIV‐1 interactions with host proteins

Abstract: Productive HIV-1 infection depends on host machinery, including a broad array of cellular proteins. Proteomics has played a significant role in the discovery of HIV-1 host proteins. In this review, after a brief survey of the HIV-1 host proteins that were discovered by proteomic analyses, we focus on analyzing the interactions between the virion and host proteins, as well as the technologies and strategies used in those proteomic studies. With the help of proteomics, the identification and characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 144 publications
0
12
0
Order By: Relevance
“…However, lack of detection of Tat in exosomes from the infected cells in these two studies cannot simply be interpreted as absence of the protein. LC-MS/MS has not been detected Tat protein in HIV-producing CD4 T cells (Li 2015; Santos et al 2012; Saphire et al 2006) and in sera of HIV-infected patients (Donnelly and Ciborowski 2016). Only one study has detected Tat protein in purified HIV using LC-MS/MS in combination with micro-capillary reversed-phase liquid chromatography (µRPLC) (Chertova et al 2006), which has been shown to improve detection of low-abundant proteins such as Tat (Tomlinson and Chicz 2003).…”
Section: Discussionmentioning
confidence: 98%
“…However, lack of detection of Tat in exosomes from the infected cells in these two studies cannot simply be interpreted as absence of the protein. LC-MS/MS has not been detected Tat protein in HIV-producing CD4 T cells (Li 2015; Santos et al 2012; Saphire et al 2006) and in sera of HIV-infected patients (Donnelly and Ciborowski 2016). Only one study has detected Tat protein in purified HIV using LC-MS/MS in combination with micro-capillary reversed-phase liquid chromatography (µRPLC) (Chertova et al 2006), which has been shown to improve detection of low-abundant proteins such as Tat (Tomlinson and Chicz 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, antiretroviral drugs can control HIV replication and increase survival (2). However, current therapies come at substantial financial cost (3), and they are not curative. Moreover, if HIV patients are not medically compliant, drug-resistance and treatment-failure can ensue (4).…”
Section: M116066019 1447-1461 2017mentioning
confidence: 99%
“…Although the same protein catabolic effects in HIV infection have been recognized for a long time [ 31 - 37 ], but there are few data in the literature about infection-related amino acids and their derivatives imbalance in HIV-infected patients [ 38 - 46 ].…”
Section: Introductionmentioning
confidence: 99%